Growth, productive performance, and udder health of crossbred holstein x simmental cows and purebred holstein cows Crescimento, desempenho produtivo e sanidade da glândula mamária de vacas mestiças holandês x simental e vacas puras holandês - Knob D.A.* (2018)
© 2018 Universidade Estadual de Londrina. All rights reserved.The crossbreeding between dairy cow breeds has been used as an alternative to improve some characteristics such as milk composition, udder health, and reproductive aspects on dairy herds. The aim was to compare growth, milk yield and composition, and mammary gland health of crossbred Holstein x Simmental and purebred Holstein cows. Data were gathered from a farm located in Santa Catarina state, South of Brazil. Cow growth was assessed by weighing calves and heifers monthly. Yet for milk yield and udder health, data were taken from records of the official Dairy Herd Improvement Program carried out in the evaluated farm. These data were subjected to variance analysis using the MIXED procedure of SAS statistical software. Non-linear regressions were used to adjust the data to the growth curves. The crossbred Holstein x Simmental cows produced more milk than did purebreds (31.8 kg/day vs. 30.4 kg/day; p < 0.05), with higher contents of lactose (4.63% vs. 4.53%) and protein (3.14% vs. 3.03%), but no differences in fat content (3.00 vs. 2.96). Purebred cows had higher somatic cell score (SCS) 4.49 vs. 2.93 (P < 0.0001). Furthermore, no differences were found for the growth of calves and heifers. In conclusion, crossbred Holstein x Simmental cows have higher energy corrected milk as the Holstein ones, whit greater uncorrected milk yield only for cows with three or more lactations. Crossbreeds cows produce milk with better quality, indicated by lower SCS and higher solids content, besides showing a lower SCS and no differences regarding weight gain of calves and heifers.